PARIWISATA BERBASIS MASYARAKAT DI DESA DOPLANG: TANTANGAN DAN PELUANG DALAM PENINGKATAN EKONOMI LOKAL - Hulu, Rostina; Aryaningtyas, Aurilia Triani (STAH Dharma Sentana Sulawesi Tengah, 2024)
This study aims to examine community-based tourism development in Doplang Village, Semarang Regency, and its impact on the local economy. A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation with community leaders, tourism managers, local business owners, and tourists. The findings indicate that active community involvement in tourism management brings positive impacts, particularly in income improvement and business opportunities. However, there are challenges in terms of limited resources, infrastructure, and skills that need enhancement for more professional and sustainable tourism management. This study is limited in scope and lacks quantitative analysis. Recommendations include the need for government and private sector support in the form of training and infrastructure, as well as further research to explore collaborative strategies in community-based tourism development.